Online cash grain exchange: examining factors impacting the level of webbased trades and potential future adoption of mobile technology - Heikes, Kevin (Kansas State University, 2011)
In the grain industry, producers have sold grain for a long time over the telephone. This thesis suggests significant changes in grain marketing strategies and why other methods of selling grain may help both producers and grain merchandisers be more effective with cash grain transactions. Specifically, the use of web-based applications that allow growers to make, manage and monitor grain offers and use mobile technology for grain marketing solutions. This thesis evaluates two key technology options for agricultural producers. First, the research evaluates factors that impact traded bushels on Farms Technology’s private internet technology trading platform, the Dynamic Pricing Platform (DPP). The second element of the research defines a model which examines likelihood of growers adopting mobile trading technology to increase grain marketing opportunities. A thorough understanding of these two marketing platforms will allow Farms Technology to increase the number of growers opting to use technology to execute cash grain sales, which is financially beneficial to the company. Results indicate that a number of online variables significantly impact online grain trade, in addition to factors that specifically influence the potential adoption of mobile technology by agricultural producers. Results help quantify many insights which Farms Technology has developed in relation to online grade trading and uncovered future possibilities in the online grade trading industry. Statically significant factors that impact grain traded on the DPP include: acres (farm size), on-farm storage, percent of grain sold over the phone, offered bushels, and whether or not farmers received text messages. With respect to mobile application adoption, results identified factors that significantly and positively impact the likelihood of mobile adoption, including: farmers with no cell phone, farmers that are currently receiving text messages, farmers owning a smart phone, and customer service rating for Farms Technology by the farmer. Variables that significantly and negatively impacted mobile adoption included: farmers currently selling on the DPP and farmers who believe the online DPP application is too difficult to use.
Keywords: Grain marketing; Agriculture; Internet; Adoption; Mobile technology; Online grain trade; Agriculture, General (0473); Economics, Agricultural (0503); Marketing (0338)